Determinants of students’ generic skills and innovative behavior of science cluster: A PLS path modelling approach / Rohana Ngah, Rahimah Sarmidy and Nurul Hafez Abd Halil - Ngah, Rohana; Sarmidy, Rahimah; Abd Halil, Nurul Hafez (UiTM Cawangan Johor, 2019)
The paper aims to investigate the determinants of generics skills that influence the innovative behavior of science cluster’s students. Technology entrepreneurship has been introduced for many years for science cluster where students attend formal and informal sessions like classes and innovation and invention events. The subject focus on how students can capitalize on technology to be creative and innovative to explore entrepreneurship endeavor in future. To date, very few studies have been exploring the innovative behavior of students of science cluster from the perspective of generic skills after they had attended the technology entrepreneurship program. Thus, this paper attempts to investigate the determinants of generic skills that might influence their innovative behavior. A total of 225 usable questionnaires were analyzed using Partial Least Square software. Only creativity and proactive have a strong influence on innovative behavior while personnel support didn’t mediate the relationship between the generic skills and innovative behavior. The mixed results implied more efforts need to be done to further enhance the innovative behavior of students in preparing them to the real-world challenges. It is timely to readdressed on how to further improve and strengthen generic skills of students. Recommendation and suggestion are presented.